Perlindungan Hukum Terhadap Pengguna Jasa Influencer Dalam Pemasaran Produk Barang Dan Jasa Untuk Membangun Sebuah Brand Melalui Promosi Di Media Sosial - Gede Agus Darmawan; I Nyoman Putu Budiartha; I Ketut Sukadana (Jurnal Analogi Hukum, 2025)
Businesses utilize social media to promote their products using influencers. The use of influencers, namely figures on social media who have a large number of followers. Business actors get endorsement offers. In the endorsement there is a cooperation agreement between the business actor and the influencer, which often occurs by default by the influencer. This research aims to analyze the form of protection for business actors in the event of default by influencers. The problems are 1) How is the legal regulation of promotional activities carried out by influencers as promotional media on social media? and 2) How is the legal protection of business actors in using influencer services in the event of default? The research uses normative legal studies with a statutory approach and conceptual approach. The legal materials used are primary and secondary materials. The technique of collecting legal materials uses the method of literature study (library research) and recording. Analysis of legal materials using descriptive analysis The results showed: regulation of influencers can be found in various laws, namely Law No. 8 of 1999 concerning Consumer Protection, Law No. 32 of 2002 concerning broadcasting, Law No. 19 of 2016 concerning ITE.